2004
DOI: 10.1073/pnas.0404016101
|View full text |Cite
|
Sign up to set email alerts
|

Varicella-zoster virus infection of human neural cells in vivo

Abstract: Varicella-zoster virus (VZV) establishes latency in sensory ganglia and causes herpes zoster upon reactivation. These investigations in a nonobese diabetic severe combined immunodeficient mousehuman neural cell model showed that VZV infected both neurons and glial cells and spread efficiently from cell to cell in vivo. Neural cell morphology and protein synthesis were preserved, in contrast to destruction of epithelial cells by VZV. Expression of VZV genes in neural cells was characterized by nuclear retention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
31
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 39 publications
1
31
0
1
Order By: Relevance
“…There have been four other studies of VZV interaction with human neurons in vitro (2,13,14,21). All were different than ours in that neuronal infection was established by cocultivation rather than with cell-free virus, and only one of the studies analyzed neurons for VZV gene expression weeks after infection (21).…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…There have been four other studies of VZV interaction with human neurons in vitro (2,13,14,21). All were different than ours in that neuronal infection was established by cocultivation rather than with cell-free virus, and only one of the studies analyzed neurons for VZV gene expression weeks after infection (21).…”
Section: Discussionmentioning
confidence: 82%
“…The second study by the same laboratory also infected explants of human fetal dorsal root ganglia and showed that productive virus infection peaked at day 4 but dropped dramatically by day 5 (13); infected neurons were not analyzed weeks later, which would have allowed a comparison of viral gene expression with our neuronal cultures. The third study used human neural stem cells isolated from fetal brain that were transplanted into nonobese diabetic SCID mouse brains, after which they were allowed to differentiate in vivo, followed by infection with VZV (2). In this chimeric model, VZV was found in both neurons and glial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in a model of VZV latent infection using cotton rats, ORF63 recently has been shown to play an important role in the efficient establishment of VZV latency in these animals, although the mechanism underlying this function remains to be defined (8,9). Several novel systems for investigating the neurotropism of VZV in vivo using chimeric NOD-SCID mouse-human neural cells or intact DRG xenografts also recently have been described (4,38). Studies using the chimeric NOD-SCID mouse-human neural cell model found that cells infected with the single-copy mutant of ORF63, rOka⌬ORF70, showed the same cellular localization as pOka and vOka, which have two copies of ORF63 (4).…”
Section: Discussionmentioning
confidence: 99%
“…Grafting of neural cells has been used to examine infection of neurons and glial cells (2). In a variation of this model, intact human fetal dorsal root ganglia (DRG) have been grafted into SCID-hu mice to show that after initial productive infection, VZV persisted in a form consistent with the establishment of latency (29).…”
mentioning
confidence: 99%